THE IMPACT OF EDUCATIONAL PROGRAMS ON NURSES’ COLLABORATION WITH PATIENTS AND FAMILIES - Tagreed Ghazi Alenzi, Dalal dhahawi Aldhafeeri, Dalal dhahawi Aldhafeeri, Farhan Ayed Aldhafeeri, Fawaz Aiyed Aldhafeeri, Naji Suwied Alanzi, Sami Bader Alanazi, Abdulaziz Mamdouh F Alanazi; Faiza Mater Faris Al Dhafeery, Thamer Mateb Alkhaldi, Mamdouh suwayyid Alanazi, Rabiah Farhan Holal Alanazi, Laila Mulfi Braim Alsaadi, Abdulkarrm Nahabah Aldhafeeri (Chelonian Research Foundation, 2022)
Evidence suggests that the individual receiving care, the family, and nursing staff all benefit from the application of family nursing concepts to practice; however, family nursing is inconsistently and inadequately implemented in clinical practice settings. A potential factor at play could be the presence of inadequate or insufficient educational curricula pertaining to family nursing. A comprehensive examination of the research examining the efficacy of family nursing training courses designed to promote clinical proficiency in family nursing is presented in this article. A comprehensive review of six databases yielded fourteen studies that satisfied the inclusion criteria. This process identified three overarching themes: general research features, components of educational programs, and outcome measures. While these educational programs purportedly enhanced family nursing understanding, abilities, and mindsets, they failed to assess the nurses' practical application and assimilation of clinical competencies specific to family nursing. The implications of this review are pertinent to both research and family nursing education, particularly in the context of future program design and evaluation. The process and outcomes of the most effective methods in family nursing education, as well as their implementation and evaluation in actual practice settings, must be the subject of additional investigation in the future. Keywords: educational programs, nurses, collaboration, patients, implementation and evaluation, families.